2006
DOI: 10.1021/jf052066p
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Content of 50 Watermelon Cultivars

Abstract: The lycopene content of 50 commercial cultivars of seeded and seedless red-fleshed watermelons was determined. Scanning colorimetric and spectrophotometric assays of total lycopene were used to separate watermelon cultivars into low (<50 mg/kg fw), average (50-70 mg/kg fw), high (70-90 mg/kg fw), and very high (>90 mg/kg fw). Cultivars varied greatly in lycopene content, ranging from 33 to 100 mg/kg. Most of the seeded hybrid cultivars had average lycopene contents. Sixteen of the 33 seedless types had lycopen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
91
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(105 citation statements)
references
References 17 publications
11
91
1
2
Order By: Relevance
“…The profile and content of inajá oil described in Table 2 and Figure 3 are completely new, as only the total carotenoid value, around 150 mg·kg −1 found within the dry pulp of fruits has previously been published (Telles, 2006), which are similar to those values obtained in this study (Table 2). The high proportion of lycopene in its oil (33%) is a significant novelty in palms oils with a content of 30 mg·kg −1 that fits with that found in papaya or watermelon (Perkins-Veazie et al, 2006;Souza et al, 2008). Similar values have been quantified for ß-carotene, the carotene that is most present in this oil, followed by γ-carotene and α-carotene.…”
Section: Resultssupporting
confidence: 77%
“…The profile and content of inajá oil described in Table 2 and Figure 3 are completely new, as only the total carotenoid value, around 150 mg·kg −1 found within the dry pulp of fruits has previously been published (Telles, 2006), which are similar to those values obtained in this study (Table 2). The high proportion of lycopene in its oil (33%) is a significant novelty in palms oils with a content of 30 mg·kg −1 that fits with that found in papaya or watermelon (Perkins-Veazie et al, 2006;Souza et al, 2008). Similar values have been quantified for ß-carotene, the carotene that is most present in this oil, followed by γ-carotene and α-carotene.…”
Section: Resultssupporting
confidence: 77%
“…The greater potential for nitric oxide synthesis after watermelon juice supplementation might be linked to a synergistic effect between L-citrulline and other constituents of watermelon juice. For example, watermelon juice is high in the non-enzyme antioxidants, glutathione, lycopene and β-carotene [34][35][36], which can scavenge the superoxide radical [37,51]. This is important given the rapid reaction of superoxide with nitric oxide to form peroxynitrite which compromises nitric oxide bioavailability [52].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, watermelon is rich in many antioxidants in addition to glutathione, including lycopene and β-carotene [34][35][36]. Lycopene and β-carotene may increase nitric oxide bioavailability since they have been shown to blunt the scavenging of nitric oxide by superoxide [37].…”
Section: Introductionmentioning
confidence: 99%
“…Lenucci et al [40] showed that the content of lycopene and b-carotene varied significantly among 14 cultivars of cherry tomatoes. Likewise, the total carotenoid content ranged from 3700 to 12 200 lg/100 g among 50 cultivars of red-fleshed watermelons from US [45]. Wall [24] studied composition of different cultivars of banana and papaya.…”
Section: Genotype Effectsmentioning
confidence: 99%